2016
DOI: 10.1111/jfd.12564
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance and repetitive‐element PCR fingerprinting in Aeromonas veronii isolates

Abstract: This study evaluated antibiotic resistance and the related genes in total 47 Aeromonas veronii isolates from pet fish, eel (Anguilla japonica) and koi (Cyprinus carpio) in Korea. In comparison with the antibiotic susceptibilities of isolates from eel and koi, those of pet fish were more resistant to ceftiofur, aminoglycosides, tetracycline and nitrofurantoin. And isolates from pet fish showed high prevalences of class 1 integron, quinolones and tetracycline resistance determinants than those from eel and koi. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Multiple antimicrobial resistant Aeromonas isolates have been reported globally associated with ornamental fish and food fish culture [1,19]. Single and multiple antimicrobial resistance has been shown to commonly used antimicrobials in aquatic sector, such as erythromycin, tetracycline, chloramphenicol, nalidixic acid, and nitrofurantoin.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple antimicrobial resistant Aeromonas isolates have been reported globally associated with ornamental fish and food fish culture [1,19]. Single and multiple antimicrobial resistance has been shown to commonly used antimicrobials in aquatic sector, such as erythromycin, tetracycline, chloramphenicol, nalidixic acid, and nitrofurantoin.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies on market fish also described the isolation of Aeromonas hydrophila with 100% resistance to methicillin (Vivekanandhan et al 2002). Chung et al (2017) have also reported the high prevalence of antibiotic resistance for bacteria isolated from imported pet fish. Higher level of antibiotic resistance has also been reported previously for Klebsiella sp., and Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 66%
“…The high presence of integron-integrases elements in aquaculture has been described in several papers [30,33,57,58], even further, the presence of integrons in resistant bacteria isolated from the sediment of salmon farms in Chile has been described in a recently published paper by [56] which has even reached clinical isolates of the bacteria E. coli . Among the gene cassettes described in this work, the high abundance of genes dfrA12 and dfrA17 , which confer resistance to trimethoprim, as well as genes resistant to aminoglycosides aadA2 and aadA5 , can be observed.…”
Section: Discussionmentioning
confidence: 99%